(untitled) (Physical Culture and Sport: Scientific Perspective, 2023)
One of the ways to improve the general intelligence system is to improve the professional training of future intelligence officers and increase the level of their professional readiness to use modern methods and means of obtaining intelligence information. The purpose of the study is to generalize modern views on the process of forming professional readiness of specialists in various fields, to identify the peculiarities of formation and structure development of future intelligence officers’ readiness for professional activity, as well as to provide suggestions on possible ways of increasing the level of its formation. In the process of the research, theoretical (analysis and systematization of scientific and pedagogical literature, regulatory and legal documents, instructional and methodical materials) and empirical (study and generalization of domestic and foreign experience, interviewing combat participants and intelligence veterans, observation) methods were used, which gave the opportunity to summarize the modern views of scientists on the process of forming the professional readiness of specialists in various fields, to identify the formation peculiarities of future intelligence officers’ professional readiness and, on this basis, to develop the structure of their professional activity readiness formation. The article reveals the peculiarities of the formation of future intelligence officers’ professional readiness during their execution of combat army systems exercises, combat training standards, as well as during special training on the ground surface, underground, in water bodies, under water and in the air. The structure of future intelligence officers’ readiness for professional activity has been developed in the form of interconnected dynamic blocks (psychological, scientific-theoretical, result-activity block), which include special professionally oriented components. It is proposed: to introduce new standards, forms, methods and means of obtaining intelligence information into the process of forming the intelligence officers’ professional readiness, based on the experience of the NATO members armies and the experience gained by the intelligence units of the Armed Forces of Ukraine in the course of liberating the territories of sovereign Ukraine captured by Russian terrorist forces; to intensify the application of distance learning basic forms and standards of individual and collective training of the Armed Forces of Ukraine and NATO units.